PENGGUNAAN FRACSEAL DAN CaCO3 PADA HPWBM UNTUK MENCEGAH TOTAL LOST CIRCULATION PADA SUMUR XY1 - Lemuyaq, Guis Pangeran; Ulfah, Baiq Maulinda; Rahman, Muhammad Rizqie Fathan (PETROGAS: Journal of Energy and Technology, 2025)
Drilling mud is a crucial element factor in the drilling process, serving to clean cuttings also resolve downhole issues. High-Performance Water-Based Mud (HPWBM) is a significant advancement, utilizing polyamine to inhibit water absorption in shale and clay formations while offering ecological and economic benefits. A major challenge in drilling is lost circulation, where mud flows into formation gaps due to pressure differentials or formation characteristics. This study focuses on an HPWBM innovation using Calcium Carbonate CaCO3 and Fracseal as Lost Circulation Materials (LCM) to treat total lost circulation. CaCO3 and Fracseal act as effective plugging agents for fractures and pores. The objective is to analyze the performance of this system by evaluating the changes in rheological properties and the effectiveness of Fracseal dosages across different well sections, specifically the 17-1/2", 12-1/4", and 8-1/2" holes. The results demonstrate that this innovative mud system effectively restores wellbore stability and prevents severe mud loss, offering a viable solution that enhances safety, efficiency, and provides potential cost savings in oil and gas drilling operations.